Photocatalytic activity of anatase–nickel ferrite heterostructures. Issue 4 (20th January 2015) - Šutka, Andris; Millers, Martins; Döbelin, Nicola; Pärna, Rainer; Vanags, Martins; Maiorov, Mihael; Kleperis, Janis; Käämbre, Tanel; Joost, Urmas; Nõmmiste, Ergo; Kisand, Vambola; Knite, Maris
<x xml:space="preserve">Abstract</x> The simple co‐precipitation route was used to couple commercial TiO2 anatase nanopowder with nickel ferrite (NiFe2O4). The morphology and the crystalline structure of composite nanoparticles were characterised by TEM, N2 adsorption‐desorption, XRD and Rietveld refinement, XPS and XAS. The optical and magnetic properties were investigated. After co‐precipitation NiFe2O4 nanoparticles, composed of spinel ferrite crystal phase, were formed on the surface of TiO2 anatase nanopowder. The TiO2/NiFe2O4 composite oxide demonstrated large specific surface area, high visible light absorption efficiency and efficient charge carrier separation, compared to pristine anatase TiO2 or pristine NiFe2O4, representatively. The obtained TiO2/NiFe2O4 composite oxides, with different nickel ferrite contents (5, 10, 25, 50 and 75 wt%) showed decent visible light photocatalytic efficiency, up to three times higher than pure anatase or pure NiFe2O4. However, TiO2/NiFe2O4 composite oxides did not demonstrate high magnetic properties.